A Cross-Sectional Study on Morphometric Variations of Nasal Morphology in an Ethnic Population of Soth India - Manoj Premraj 21B10102; Dr. Nitin V. Muralidhar (JSS AHER, Musuru JSSDCH , Mysuru, 2024)
1. Introduction 2.Aim 3.Literature Review 4. Materials & Methods 5. Results 6.Discussion 7.Conclusion 8. summary 9. References 10. Annexure